Compressive behaviour of novel timber-filled steel tubular (TFST) columns. (30th March 2020) - Karampour, Hassan; Bourges, Mélanie; Gilbert, Benoit P.; Bismire, Andrew; Bailleres, Henri; Guan, Hong
Highlights: Novel timber-filled steel tubular (TFST) columns are proposed and fabricated. Short and long TFST columns are tested in axial compression. Analytical expressions and finite element analyses (FEA) models are developed to explain the test results. Results suggest that TFST columns can be a potential substitute for concrete-filled steel tubular (CFST) columns. The proposed product may offer a market to the non-graded (low Modulus of Elasticity) sawn lumbers. Abstract: Timber-filled steel tubular (TFST) columns are proposed and fabricated in this paper using a novel manufacturing method without using glue or mechanical anchoring devices. Stub ( L  = 200 mm) and slender ( L  = 1500 mm) TFST columns with low-grade and high-grade timber inserts are manufactured, and are tested in compression. Analytical expressions and finite element analyses (FEA) models are developed to explain the test results. Using the validated FEA models, slenderness curves are established, and boundaries for classification of stub and slender columns are defined. Results show that the stub columns reach the ultimate capacity predicted by the analytical expression within 1%. The slender columns buckle at loads lower than the suggested analytical elastic composite buckling load. The FE stress analysis shows that in short and long columns the failure initiates in timber and steel, respectively. The average ultimate capacities of the tested stub and slender high-grade columns are found to be 29% and 24% higher than those of the low-grade columns, respectively. Results suggest that TFST columns can be a potential substitute for concrete-filled steel tubular (CFST) columns, due to the lightweight of timber infill and its high compressive strength in the fibre direction. Moreover, the proposed product may offer a market to the non-graded (low Modulus of Elasticity) sawn lumbers.